2019
DOI: 10.1186/s41747-019-0115-4
|View full text |Cite
|
Sign up to set email alerts
|

Artefact and ablation performance of an MR-conditional high-power microwave system in bovine livers: an ex vivo study

Abstract: Background We evaluated a magnetic resonance (MR)-conditional high-power microwave ablation system. Methods An exvivo 1.5-T evaluation was conducted by varying the sequence (T1-weighted volume interpolated breath-hold examination, T1w-VIBE; T1-weighted fast low-angle shot, T1w-FLASH; T2-weighted turbo spin-echo, T2w-TSE), applicator angulation to B0 (A-to-B0), slice orientation, and encoding direction. Tip location error (TLE) and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…The formation of air bubbles during ultrasound-guided ablation results in a blurred boundary. Thus, MR-guided ablation plays a very important role in the ablation of very small lesions and lesions at speci c locations 25,26 It has been reported that poor display microwave applicator tip (length, 1.6 cm) on T1WI may be related to the ceramic structure of the tip, especially for oblique non-coplanar puncture, but the depth and shape of the applicator tip can be observed better after scanning along the long axis of the microwave applicator 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The formation of air bubbles during ultrasound-guided ablation results in a blurred boundary. Thus, MR-guided ablation plays a very important role in the ablation of very small lesions and lesions at speci c locations 25,26 It has been reported that poor display microwave applicator tip (length, 1.6 cm) on T1WI may be related to the ceramic structure of the tip, especially for oblique non-coplanar puncture, but the depth and shape of the applicator tip can be observed better after scanning along the long axis of the microwave applicator 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, one relevant issue regarding patient safety concerns the visualization of the microwave applicator. In our recently reported ex vivo evaluation of the appearance of the applicator’s MR artefact, the applicator shaft was clearly visible under MR guidance while the tip only showed a small artefact [ 17 ]. This observation was even stronger under clinical, non-optimal conditions, especially with MR-fluoroscopic sequences.…”
Section: Discussionmentioning
confidence: 99%
“…3D T1-weighted VIBE was repeated to confirm the correct applicator position. The previously reported impaired visibility of the applicator tip had to be considered during applicator placement and position control [ 17 ]. Ablation was conducted after connection of the microwave antenna and the generator via an MR-compatible coaxial cable with the generator placed outside the scanner room.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antenna was attached to the microwave generator (ECO-100E2, Nanjing ECO Medical Instrument Co, China). 21,22 It generated electromagnetic waves that agitate water molecules in the surrounding tissue, producing friction and heat, thus inducing cellular death by coagulative necrosis. A pre-set mode with output power of 55 to 80 W was used with duration of 5 to 15 minutes for each ablation.…”
Section: Immunohistochemical Methodsmentioning
confidence: 99%